EFFECT OF SEASON ON METABOLITES AND SEMEN TRAITS OF BULLS - F. G. AL-Gebouri; S. M. Eidan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to investigate the effect of the winter and spring seasons on some biomarkers and semen characteristics of Holstein bulls (n = 20) during the Coronavirus pandemic period. Semen was collected for 16 weeks and evaluated weekly, along with the determination of some biomarkers. Sperm concentration, live sperm percentage, the concentrations of the most amino acids, essential, non-essential, and total amino acids, all carboxylic acids, omega 3, 6, 9, total fatty acids, and total saturated and unsaturated fatty acids, increased (P